Avaliando as potencialidades de um game para o ensino e a aprendizagem de Língua Inglesa - Asega, Fernanda Katherine (2015)
This research, conducted in the area of Materials Evaluation and Design for Language Learning, more specifically the English language, and games as a research object. Technological innovations have enabled access to information by transforming the means and modes of communication. Currently, the integration of digital technologies in language learning and teaching practices is growing, given that young people are constantly connected to the web, interacting with several people and tools such as games. These tools work extending cognitive ability, abstract thinking and language functions. The purpose of this study is to analyse what potential the game World of Warcraft offers for teaching and learning the English language, in order to be used as teaching material aimed at teenagers and adults who need/want to learn the language. The decision to use such game was based on its popularity around the world. As one of the media most used by young and likely to be a known and common language between them, they can facilitate learning processes that lie in more familiar contexts for students. Given the above, this study examined the game World of Warcraft in its potential as a teaching and learning materials for English language for teenagers and adults. The theoretical background of this study is based upon the concepts of Cyberculture (LEVY, 1999; LEMOS, 2005), Connectivism (SIEMENS, 2004, 2007, 2008; DOWNES, 2012), Participatory Culture, addressing the skills and abilities necessary for education in the twenty-first century (JENKINS et al., 2006), Learning in Games (GEE, 2003, 2008, 2010, 2012, 2013; PRENSKY, 2001, 2005) and Materials Evaluation and Design for Language Learning (RAMOS, 1999 / 2009, 2009). The study was submitted to the possibilities for teaching and learning the English language from the perspective of cyberlearning and related to the use of language. When analysed from the perspective of cyberlearning it was emphasized the importance of problem-solving situations, interactions and transmedia skills and activities identified in the game as English teaching and language learning opportunities. When analyzed the possibility for teaching and learning of English language related to the use of language, the features and the contents were examined which can be exploited in the development of teaching materials through this game. For this, data were categorized as resources, content and texts. The game analysis made it possible to demonstrate its potential for use in the English language (cyber)learning, in which the development of performance and simulation skills are essential in the current scenario. This paper concludes that this game's potential use in teaching and English language learning is attributed to situations of problem solving, in which students can develop all presented subcategories, especially transmedia so that students can follow the flow of stories, when confronted with the information available in different media formats, making it possible to fulfill the process of teaching and learning